2013
DOI: 10.3389/fimmu.2013.00425
|View full text |Cite
|
Sign up to set email alerts
|

Low GILT Expression is Associated with Poor Patient Survival in Diffuse Large B-Cell Lymphoma

Abstract: The major histocompatibility complex (MHC) class II-restricted antigen processing pathway presents antigenic peptides acquired in the endocytic route for the activation of CD4+ T cells. Multiple cancers express MHC class II, which may influence the anti-tumor immune response and patient outcome. Low MHC class II expression is associated with poor survival in diffuse large B-cell lymphoma (DLBCL), the most common form of aggressive non-Hodgkin lymphoma. Therefore, we investigated whether gamma-interferon-induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 52 publications
0
29
1
Order By: Relevance
“…Previously optimized staining protocols for GILT and MHC class II [5] were modified to use a red chromagen in order to avoid confusion of melanin pigment with a brown chromagen. Formalin-fixed, paraffin-embedded tissues were sectioned at 3-5 μm and mounted on charged glass slides.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously optimized staining protocols for GILT and MHC class II [5] were modified to use a red chromagen in order to avoid confusion of melanin pigment with a brown chromagen. Formalin-fixed, paraffin-embedded tissues were sectioned at 3-5 μm and mounted on charged glass slides.…”
Section: Methodsmentioning
confidence: 99%
“…GILT serves a unique function of reducing protein disulfide bonds in the endocytic compartment, as GILT is the only reductase known to reside in this compartment. Previously, GILT has been shown to be constitutively expressed in professional antigen presenting cells (APCs), including B cells, monocytes/macrophages and bone marrow-derived dendritic cells [3-5]. GILT expression can be induced in other cell types such as melanoma cell lines by interferon (IFN)-γ [6].…”
Section: Introductionmentioning
confidence: 99%
“…This caused immune tolerance or unresponsiveness to leukemia antigens and lead to a significantly shortened disease-free survival of patients with AML or diffuse large B-cell lymphoma. 23,65,66 In contrast, some CLIP ¡ tumor cells were able to process li-independent endogeneous antigens generated by the proteasome for HLA class II-restricted presentation thereby activating TAA-specific CD4 C T cells. 23,67 Furthermore, it has recently been suggested that the different HLA class II phenotypes in tumors can be controlled at the post-transcriptional level, in particular by microRNAs (miRs).…”
Section: Deregulation Of Hla Class II Apm Components In Malignant Cellsmentioning
confidence: 99%
“…Levels of GILT expression are often associated with poor patient survival, indicating an impaired presentation of class-II-restricted peptides (47). Further, lower GILT expression reduced CD4 + T cell-mediated responses in in vivo mouse models (4850).…”
Section: Discussionmentioning
confidence: 99%